CODESRIA Bulletin Online, No. 10, October 2020 - Derilict Shards: The Roaming of Colonial Phantoms - by Yvonne A. Owuor - Yvonne A. Owuor (CODESRIA Bulletin, 2020)
Online keynote address given at the International Conference: Colonialism as Shared History. Past, Present, Future, 7–9 October 2020, Berlin. Organized by Ulrike Lindner, Bettina Brockmeyer, Rebekka Habermas, Gerda Henkel Foundation and the German Federal Foreign Office. Honourable Minister, Michelle Müntefering, Professor Drs Rebekka Habermas, Bettina Brockmeyer, Ulrike Lindner, ladies and gentlemen, good afternoon from my side of the world. Nicole Gonsior, Katharina Klaus, Simone Baumstark—thank you for all your support. To the panellists, audience—some of whom are friends signing in—a huge hello. I trust that you are all holding up well in these surreal days. A quick apology My presentations are usually companioned by dramatic visuals, mostly collated from the public library that is the World Wide Web. Copyright issues associated with this session mean I have to forego the visual evidence. When Professor Dr Rebekka Habermas contacted me to inquire whether I would be interested in offering a keynote, I reminded her that I am a person of artistic persuasion, not an academic. ‘That’s what we desire,’ she replied. I asked if she was aware that I do not have a single politically correct bone in my body. She said, ‘Good.’ ‘I eat sacred cows,’ I pleaded. She implied, ‘Guten Appetit.’ So here we are. Derelict shards An opening quotation by the late Swedish author, Sven Lindqvist, who for me represents those rare human beings who do the hard work of refining and engaging a sense of their moral consciousness and conscience, however disordering that can be, from his extraordinary work, ‘Exterminate All the Brutes’: One Man’s Odyssey into the Heart of Darkness and the Origins of European Genocide: in the first paragraph, he observes ‘You already know enough. So do I. It is not knowledge we lack. What is missing is the courage to understand what we know and to draw conclusions.’ I concur. So this is a very preliminary incursion into what I trust will later be a thorough excavatory process. Some figurative bodies might be exhumed and raise a stink. I don’t apologise. In this offering, Aimé Césaire and Frantz Fanon make technical appearances, as do other thinkers. Fanon and Césaire are reminders that the road maps already exist. It is the will to change ourselves through implementing their prophetic imperatives that has been absent. Also. About Africa. For this presentation, do hold its giant and complex pluralities in mind. I refer to the whole of Africa, the pluriversality of it, its essential diversities. There is no subbing of the Sahara in my Africa. Its territoriality extends beyond the seas, its tentacles touch every space that exists in the world. And, although I am Nairobi and Kenya born, bred, formed and identified, the Occident has and does inform and influence me; this is an intrinsic part of the multiplicities I contain and I live my paradoxes with ease. Next NB: History is a palette for me. I do prefer, it is true, the older and longer histories of my people. As brutish as the fairly recent encounter of Africa with the Occident has been, as soul-damaging as it still is, that encounter, in the scheme of our lives, is but a small, viciously irritating footnote in the longer trajectory of our existences. The stories of our shared encounters are myriad, diverse and dispersed. It is not a monolithic tale. We do have in common our experience of you, the Occident, the metaphor, symbol, the relation of you. You. Sie. It is this ‘you’ that this reflection also attends to. I think, before we can arrive at a ‘we’, we must exhaust the accusative ‘you’, ‘Sie’, not directed at the individual, but to a particular and historical cultural position, idea and consciousness and its world-making choices. The German colonial idea is a part of the Occidental colonial imperative, was informed and inspired by it. ‘Shared’: interesting word. However, we must prioritise, attending to the ‘us’ in community and later in the collective before we can finally arrive at a shared ‘we’. Also, because the colonialism catastrophe did not unfold in isolation, the ‘we’ encompasses other nonAfrican and non-European worlds, which I hope are enjoined in this project, if not the conference. Now. This paper went through two major revisions, and I use these to set out a context. The first version prepared for—was it May?—offered a point of view that called for a forensic historical reckoning to help stay an inevitable coming explosion of rage. That became moot when fault lines were created by the grotesque public lynching of the human being, Mr George Floyd, and rumblings started all over the world. A second revision was inspired by the worldscape created by the ongoing visitation of the coronavirus. I was startled by the discombobulations and public health disorders of societies that have behaved for the last eighty years as if they were exempt and excused from the vagaries of human suffering, that have treated the sufferings of others in the world, like the nations of Africa, as an intrinsic flaw in their nature. Around that time, I also happened upon a commentary on the June 2017 World Bank Pandemic Emergency Financing Facility and the ‘pandemic bonds’1 they had floated. The investor nations included the European Union; the USA, of course; Japan. The bonds were oversubscribed. This bunch was betting heavily on reaping profits out of pandemic-caused mass deaths, primarily in Africa and possibly in Asia. These bonds were to ‘transfer pandemic risks in low-income countries to the financial markets’. Put simply, here was the commodification of anticipated suffering, the instrumentalisation of anguish for profit. The human scavengers then proceeded to package their macabre money-grubbing and obscene feeding frenzy as philanthropy. My visceral disgust focused this presentation. It is now an aetiological enquiry. There is an urgent human need to interrogate a 400-year-old cultural mindset. How does a dynamic culture get to lose grip of the basics of being human? How does this culture come to justify and then amplify its dependency on its predation of other humans? Is there any precedent for a culture seeing itself and intentionally undertaking a long-history probing of its cultural conscience and collective soul? In the pandemic bond subscription story I found a perfect condensation of the essential character of the European imperialism and colonisation project. Colonialism as shared history? A rephrasing of the theme is probably required. When a psychopath enters a family’s home and proceeds to rape, rob and murder, and then takes over the family pet, the premises and lands, grows grapes on these, mines the gold he finds there and becomes extremely wealthy in the process, later becoming host of the most elegant classical music soirées that are celebrated to great acclaim, no matter what, that brutalised, displaced, victimised family, if any of them do survive, cannot later engage with the atrocity that annihilated them as a matter of shared experience. The inhumanity, the violation of the basic covenant of human relationality, the desecration of dignity and decency forbid it. With very few exceptions—I can’t think of any—the forced entry of Europe into other worlds remains a horror story of brutishness, cruelty, violence, predation and inhumanity. What might a descendant-beneficiary of such a heinous crime do when confronted with the reality of this scenario, and finding a spark of human horror within seeks to at least understand? Enter into the worlds of the most shadowy of memories; undertake to collect and collate memory of the crime scene; approach with utter reverence the weight of tragic knowing that descendants bear. Witness. Attend to the truth (capital ‘T’). Find a language for the experience of that understanding. Translate into heartfelt grief. Speak it out to an other. Listen. Repair. There are no expiry dates for acts of human reparation. Aimé Césaire: ‘No one colonizes innocently, … a nation which colonizes, a civilization which justifies colonization—and therefore force —is already a sick civilization …’. I worry that unless a wilful effort is made to dig around the historical roots of the genesis of what becomes the colonial enterprise—I mean the human mindset and sequence of experiences and thought and cultural compromises that converged to make it unfold in the anti-human way that it did, yet another long season of good minds rambling round and round a dry watering hole will unfold. There are important questions waiting for all of us at the roots. I need to understand, for example, as a human being perplexed by the depth and intensity of evil, and who, with a billion others, still lives out colonialism’s resonances and discontents, what was in the European cultural psyche that turned such an excess of its migrating population into sociopaths, psychopaths and serial killers operating in the world? This is abnormal by any historical standard. Why did it happen to Europe in particular, in the way that it did? Knowing the codes of life, hiding the intrinsic sadism under the veneer of Judeo-Christianity with its thoushalt-not-kill, thou-shalt-not-covet, love-thy-neighbour-as-thyself tenets, in confronting the other, why was there such a wholesale failure of faith as life and action? Future research processes, probably by combined teams of forensic pathologists, anthropologists and psychoanalysts, might uncover some of the reasons for this aberration, which then proceeded—mostly through a hitherto unexperienced will to violence, will to annihilate masses, will to genocide—to turn its derangements into laws of and for the world. By the way, I use the metonym ‘Occident’ to refer to the ideological space from which the originators and architects of the catastrophe that became colonialism emerged, for the sake of aetiology and the tomb-poking process that is this presentation. Oh yes, about those pandemic bonds … Good news. Fortunately for humanity, the winds of fate do sometimes blow fairly. Covid-19, that equal-opportunity existential threat, has caused the would-be vampires to join the rest of humanity in reflecting on the meaning of human vulnerability and mass suffering, of dealing with uncertainty and making peace with the unknown. The paper on which the bonds were printed is bulkier and more valuable than the anticipated returns on investment. And this year, the World Bank ditched its second offering. A shared history? There is a one-word answer to the implied question. What we share most in history is the Greek word, trauma. But what to do with it when trauma is a multiprism, multi-form, distinct-character presence? At the core of the tragedy of colonialism is the sadness of wilful destruction of the gift and treasure of the intimacy of humanity, of what-could-havebeen. What we lost by the violence and hubris of this encounter-madetragic was each other. Derelict Shards—the conference’s title references jutting, sharp and pointy bits that still pierce our ease with one another; phantom pieces of shrapnel from the fallout of our fatal encountering in this ghostmaking project, not aided by the faux-innocence and deliberate amnesia that sweeps our many restless dead (yours and ours) under metaphorical carpets. You wanted a speech. I have none to give. If a type is required for this presentation, then call it a dirge, or an introit for a requiem, or a literary autopsy. A dirge is a call for introspection for the dirge-singer, bereaved family, community and the deceased, whose life, most African cultures understand, is a continuum. The dead must still account for the meaning of their choices, their existence and the effects their lives had on others. There is a witness. The dirge is a site and space of, among other things, argument, audit and debate. The dirge is a site of witness and also outpouring and acknowledgment of the pain of grief. Oh yes, after the dirge has detailed the things that need to be shouted out, the dirge-singer is at once forgiven and is not held accountable for things heard. (I am indemnifying myself, here.) The dirge becomes an outlet for the release of the ghosts that would lurk restless, for the sorrow that might consume its holder, for the deceased that died afraid that they would be forgotten. Another point: I find that I treasure the word ‘autopsy’,2 in its etymological and aetiological sense, as a method of inquiry. Autopsy, ‘see for yourself’ in naked, unvarnished truth the innards of what is before us in a prosaic and philosophical quest. For colonialism’s form-changing, euphemism-dolling phantoms, I wish to offer a ruthless autopsy service. This presentation unfolds in a literal, digital and metaphorical Berlin: a city one cherishes, yet a city that is also in itself an unsecured multi-level crime scene of historical proportions. I heard a tentatively hopeful question behind the provocative conference title. Here is my position: It is still premature to ask it. You see, we have not yet even evolved a philosophy or grammar for the reconciling of our rattling skeletons, those dread phantoms and sometimes frolicking ghosts that roam the carnage of the devastated landscapes of tragically generated pasts that leach into the present with a lack of acknowledgement, with excessive noise, with ceaseless conceptualising and abstraction, and with which we collude to do nothing, and through this do-nothingness suffocate the life and keep sealed the doors of hope for a robust, living, human future between us. Back to aetiology. Sie. You. The Occident—not just Germany As with many shape-changers founded on ether, the Occidental notion always reshapes and reforms itself. Where are we now? The Five Eyes Alliance? The North, the West, Developed, First World, Nirvana? What is your presently trending metonym? Anyway, the idea of the Occident was given a dogmatic imprimatur through the 7 June 1494 Treaty of Tordesillas and an associated Papal Bull that launched the alleged Age of Discovery. Didn’t anyone ever think to interrogate such a ridiculous demarcation of worlds? No? Then, let us jump centuries. Timeline: Berlin (15 Nov. 1884–26 Feb. 1885) A summit of the leadership of the world’s thieves who gathered ostensibly to resolve the Europe-created questions connected with the Congo River basin in Central Africa, but also to apportion a continent of cultures, kingdoms, nations and peoples with no sense of the will to genocide of those who would be imposing themselves upon them in order to satiate their lusts, avarice, bloodthirst. They would secure territorial rights through carrying out a long, mostly asymmetrical war, flying the twin Trojan Horse figleaves of a civilising mission and the spread of the Gospel of Jesus Christ, which they didn’t believe in and which had deeper and older roots on that continent than in Europe. In this event, the real human motive—avarice, wealth, power— was hidden. Everything was made to sound like philanthropy. The next-level game in the ‘we-areplundering-killing-maiming-destroying-you-really-for-your-owngood’ ethos. Soon after, murderous European hordes, mandated by their home nations, would fan out across an ancient continent, looting, burning cities to the ground, committing mass murder, erasing humans; raping, spreading thirteen different diseases (ranging from dengue fever to syphilis, measles to the plague); rewriting histories so that, years later, an apparently educated French president, Sarkozy, would stand in what had been a trans-oceanic, transmodern trading centre systematically distorted by his earlier compatriots, and confidently state that Africa had no history to speak of, until … the European.3 The ‘shards’ There are a trillion ‘pieces’ of ‘colonialisms’ scattered across our worlds, transcending borders and time and space. Your museums, collections, libraries filled with looted artwork, power objects, documents that bear testimony to the egregiousness of your ancestors’ acts, the intrinsic evil of this catastrophe. Yet these do not translate to your Occidental publics as anything meaningful, or human. Mr Sarkozy’s education, with its cultivated blindness, did not allow him to connect the Senegalese high-value looted artwork, the elaborate cultural items, the human body parts in French stolengood clearing houses also called museums and collections with the young people he addressed in the city where his compatriots in the more overt colonial era had acted out those crimes. It is the unreflective conscience, the morally voided soul that can speak such poetic twaddle with intensity and confidence and behave confused when challenged. Do you wonder what psychological processes allow one culture to project a void upon an older, grander continent and all its people while transporting and hoarding the bounty of its civilisations in its cities? What psychic force gives confidence to a European to affirm the sobriquet of ‘cannibal’ to another when it is to Europe that the ripped-up body parts of our numerous dead, the murdered, are transported, are kept, are fetishised, are stored and are even debated over? You, Germany, with your shrines and reflections on the devastation of the Shoah, where there is to this moment a dispute about what to do with stolen, appropriated, desecrated human remains, the sad evidence of the Occident’s shocking, gruesome crimes against humanity, by ancestors of whose lineages you are aware. That this depth and scope of unadulterated evil does not even seize your national conscience says everything that needs to be said, not only about our fundamental disconnect, but the fact that the site where the most difficult work needs to be done between us is in the struggle towards re-humanisation. What does it mean for you to be human, Germany? What will it take? Let me take this dirge an octave higher. For your culture and peoples, colonialism was only your obscene worship of the golden calf, your dedication to Mammon to which you gave over your souls in order to seize power, wealth and control at the expense of human existence and the rights of nature. You suffocated your own humanity, plunging the earth into grief, tragedy, anguish, horror. And you still refuse to reckon with that reality, with your disease distribution and your bewildering necrophilia, to which you are so attached; you compound your horrible murderous acts with a shocking inability to agree to return the dead home. You would rather see them in display cases or jars, wouldn’t you? Shared colonialism? Which of the thresholds of our discontent do we cross into first? Epistemic, Economic, Theological, Scientific, Conceptual, Ontological, Philosophical, Historical, Linguistic, Cultural, Militaristic, Technological, Biological, Civilizational, Imaginational, Aesthetic, Teleological, Psychological, Typological, Natural? Pathological? There is tangible historical evidence to go with each of these and other unmentioned categories. Let’s do this: Open the crypts today, exhume the graves and put out the formaldehyde bottles where you have stored the bodies and body parts of our desecrated dead, and invite a pathologist to generate a report. That is an historical document too, isn’t it? These pieces of colonialism are in your midst. Why are my ancestors’ bodies and body parts still mouldering in your museums, those shrines to that gesture to the thieving souls of your ancestors? Why are you still struggling with respectfully returning the deceased home? Talk to us. Is it that you believe that by keeping them you are able to retain a powerful and magical hold over our lives? Are these your vibranium? But seriously, how will we ever bridge the fissure of the daily airbrushed Occidental conscience regarding Africa’s humanity? Will you dare to name the bones of our people you still have in your museums, collections and storerooms? And while you are at that, close down your awful zoos. They are the evidence to the extent to which your acquisitive savagery extended itself to nature. Must you possess what belongs to others even at the expense of their right to life where they best thrive? Sharing colonialism? I think somewhere there might be an East African Savannah Giraffe named Gretel suffering uncommon winters in an enclosure. Why? Colonialism—in the past? My dears, it is only a plane ride away. You have great choices: Australia, Canada, the United States of America, Brazil and New Zealand: cool destinations. Northern Ireland—yes, that too. There are also quite a few islands to choose from: Chagos, St Helena, Reunion, Mayotte, Lampedusa, the Malvinas. Are those places too far from home? Easy. Visit your museums, university storerooms, the many private collections, archived materials, your libraries. In addition, I wish to remind you of a most excellent, so readily overlooked site—the grand old banks with mandates that originated in the colonial feeding frenzy. And their records. And their listings. And their networks. The auction houses too. And how could we forget all the chartered companies representative of virtually all the nations of Europe, including the play-innocent Scandinavians? They are the mandated beneficiaries of a long, long season of plunder. What of those chartered companies that evolved into the myriad companies you uphold now as beacons of great light on a benighted world? You know them. You know why. The purpose of the colonial project was singular: acquire wealth and profit by all means necessary, even genocide. And they did so with extraordinary success. Nothing says ‘shared’ as much as do African goods building European economies for 400 years. All good. Now, in a cool, business-like way, in the interest of sharing proceeds, as part of a new historical mandate, let us research and set up an independent forensic accounting project for every one of these companies with historical associations. There is a Mount Everest of debt that has not yet been repaid in full. I suggest that in consideration of work done the interest be calculated on the outstanding debt rather than the original amount generated out of African stolen resources. And please let nobody confuse this, the settling of accounts, with reparation. That is a completely other conversation. (And you still deign to wield foreign aid at us as if you were offering us a divine favour.) We are not yet addressing the acts of violent plunder, the paid militias, the manufactured wars, the human trafficking and slave-making, the genocide mandates of all these by brutish trading companies supported by the state, institutions and the security apparatus. These too need to be examined. Was this awfulness really necessary? Given that such similar nonsense continues to this day in a place like the DRC, or even Bolivia, do you actually believe that this is in fulfilment of living out the highest human ideal? Have you ever explored this? Development Aid is your holy grail—the poverty and pity economy is a lucrative one, as the pandemic bonds show—but I trust that you know that we know that your debt to us is more than those couple of coins you roll our way? We are aware that at least 65 per cent of the resources, probably more, from our continent still sustain your economies. Does this set-up make any sense to you? Why does a system with roots in the catastrophe still persist and inform what we call ‘economy’ today? This is not just a matter of colonialism as shared; this is colonialism as continuity. By the way, I should have asked this earlier: What do you want of us now? What is your agenda this time? Our experience of you is that your interests in Africa has never been without a motive that is fully for your benefit. Tell us upfront what you want. What is in it for us? Whatever your answer, keep in mind that between us lies a chasm filled with irresolution, sorrow and suffering; of war, disease and genocide; of plunder, rape, erasure; of sustained contempt, atrocity and evil; of willed amnesia; of propaganda, rebranding, theorising and appropriation; of a life and resource debt owed, things that play out to this day. But of greater interest to many like me, as we autopsy colonialism, is to gain insight into the cultural imperative that managed to transform human beings into commodities and holds nature ransom. What sort of pathology infected the mind and culture that could do what it did? We understand that Europe has had a terribly long history with the slaughter of its own people. The reason for the ghastly Westphalian principle of sovereignty exported worldwide stems from needing to end the Thirty Years’ War, with its over eight million dead. What fed this ease with human slaughter so that this became an abiding feature of the Occidental hegemony? To explore this theme we would need to call in theologians and theologian-exorcists to work with researchers, for by asking it we understand that we enter into the realm of seeking to understand the mystery of existential evil. It is true there are only a few nations that might state that they have historically been exempt from an experience with colonisation, the occupation and domination of another’s territory, their physical, imaginative, historical and cultural life. Yet, in my experience, there seems to be a certain shudder of secret pleasure at the memory of having dominated others, a nostalgia and even longing for a return to something like that. What the Occidentals I have encountered find almost impossible to offer and engage with, a probable site of shared humanisation, are their own stories of being victimised. The Swedes I meet are reluctant to remember that their ancestors, turned into serfs in their own country, built St Petersburg in adverse weather and geographical conditions, and that a majority were worked to death doing so. As a site of inquiry, of gathering insight of the affect, might Germans consider the season they refer to, when they do, as the ‘Occupation by Allies’, as a possible site of a deep cultural woundedness that might find resonance with the colonial experiences of others? I am an outsider—so I am probably hitting a volcanic sore point, as clumsy as a bull in a ceramics shop. I mention this, because in my sojourns here, I have been struck by the telling absences, the familiar silences, the recognition of the species of ghosts, and the complexity of unease in speaking of this time. Perhaps this has as much to do with why such an occupation took place in a divided country. The gaps are interesting: the absences and silences are found in historical telling and literature: the meanings of occupation and amputation, displacement within your own home, of losing worlds, of living under the insult of mediocrities who lord it over you, and as they do so inform you that this is for your own benefit. To dare to speak, even of the meaning of this in a truthful way, is it not possible? You see, such a (good) dangerous space would subvert an expectation of an engagement that has been strongly preferred, for all sorts of reasons; a sort of power to read Africa as the pitiable perpetual victim, a scapegoat upon which much horror has been visited; an engagement that would allow the perpetrator, now in political repentance, to seize the role of restorer and administrator of balance to the once-again passive recipients, but this time of goodwill. Don’t do that. The role and power of the African space as a listener to the history of the Occidental is quite possible in the goal towards the re-humanisation of all peoples. There are immense possibilities in juxtaposing similar experiences to arrive at a human jargon of embodied histories. Uncomfortable? Good. You see, if we are to break into the heart of where our exchange becomes meaningful, transformative and future-making, then we must stand metaphorically and historically naked before each other. We traverse a tenebrous nightscape between us. It is knowledge, order and truth we seek. Drop the airs, the layers, the sophistry and associated bullshit from the get-go. Let’s go for a visceral, truthful, even messy, yet fully human engagement that we and our whole world needs, and do this with fearlessness. The instrumentalised, systematised, valorised and exaggerated fear of the other led us to this abyss in the first place. Oh! I remembered something else. My dear Germany, just what the hell was that thing you did, that reparation offer you recently made to Namibia after so many years of negotiations?4 On top of that you even tossed in that development aid covered the shortfall. Had you gone mad? Such obliviousness and mediocre engagement from you, Germany? The Nama and Herero suffered an invasion, a war, put up a spirited fight to secure their existence; they suffered a gruesome and cruel genocide, they lost their country, their worldview, their selfknowing, their imagined future; their lives were forever framed differently because of the policies of your known ancestors. We would have expected this vacuum-thinking outcome from the responsibility-denying, self-mythologising Anglo-Americans, or the perpetual-performance-of-innocence Swiss and Scandinavians, but not you, a nation that has kept a stern gaze on its chasms. Possibly there is more behind the scenes than we hear about, but the media reports suggest an historical dissonance and shockingly lazy thinking. What a missed opportunity. But I get it. There is an underlying terror that probably informs this insulting gesture. The full opening of that Pandora’s Box of reckoning would reveal the kind of skeletons that dismantle the slick veneers of imagined civilisation. To admit to an intrinsic impulse to genocide, to necrophilia, to inhumanity would damage carefully cultivated Euro identities. The African space is a scrying mirror for Occidental culture: look in it, hear from it, do not get so entranced by your reflections in it, that is not the point. More on this topic: I looked at what other imperially offending nations had offered as gestures towards meeting with and seeking to reconcile heinous pasts. You are aware of the Murayama Statement released by former Prime Minister of Japan Tomiichi Murayama on 15 August 1995, ‘On the Occasion of the 50th Anniversary of the War’s End’. Murayama apologised for, and named, Japanese war and colonial crimes and atrocities, admitting to Japanese responsibility for the deaths of millions. Can this conference imagine such an engaged cultural reckoning with conscience? By the way, no human desires another to wallow in guilt. That is selfish. Guilt will not magically change the past. What is sought and desired by the afflicted is to be seen, heard, acknowledged; to be soothed; to be given a chance to face the offender. To hear the offender accuse himself of the fault is meaningful. Such courage might unleash a treasury of options that open up the imagination of a more forgiving future. Reckoning must be written on the body, then we can really begin to experience history as shared. But I do not hold my breath. The Occident on its own volition seems incapable of the basics of such a gesture. Hubris. It is, however, likely to find the capacity when the ascendant Starship China locks into place and wishes to finally have a discussion with the descendants of the architects and perpetrators of their ‘Hundred Years of Humiliation’. Don’t hold it against us if at that time we ask China to squeeze from you our apology statement while they are in the process of collecting theirs. Speaking of China, I note with mild amusement your chattering fluster about Africa’s tryst with the East. First, Chinese historiography is intricately connected with Africa’s older and recent pasts; this is a reactivation. Second, the attraction of China? A change of script is as good as a rest. And the BRI is compelling in its vision. Third, our continent should also have bound its fate and future to the intentions and ambitions of Bandung I and II, and not pivoted westwards into a trap. A brief digression: To be clear, the type of speech I would make for an Africa-initiated process would be different. There I would speak of turning within, of observing, re-strategising with a goal to winning this overlong war of worlds; to focus on rediscovering a delirious love for ourselves and to make our nations the bounty that they are for their own. And to prioritise Asia, South America, the Middle East, Caribbean and Oceania. End of digression. Dealing with the present You know, we need to explore, together, how scholars of the world might engage with a culture addicted to a nihilistic moral disintegration; what a friend, the scholar Dr Wandia Njoya, calls suicidebomber tantrum-throwing, which threatens the rest of humanity with annihilation if it cannot seize what it wants. Have your thinkers ever reflected on why the Occident reached such a state of being in the world? I have an untested hypothesis. It is situated within and around the history of the European plague (pestilence) from mid-1300 up to 1500, which came on the back of the Great Famine (1315–17); an existential terror that penetrates the bones of the cultural spirit, a continent almost annihilated, losing 60–80 per cent of its entire population. A ceaseless season of extensive trauma and the deepest suffering would thoroughly distort any human psyche, more so if it were an act of invasion and conquest of territory by rats and fleas that neither prayer nor monarch nor army could contain. Did Europe suffer a soul wound that became a spiritual black hole? I have been struck by how much plague references show up in your lexicon regarding Africa, although we had little to do with it—you were not as important as Asia and what you call the Middle East in our economic and trade networks. But I have been curious about how much your plague shadows are cast upon the black body, upon your imagination of blackness, almost as if by doing so the revenant keeps away from Europe. It might explain some of your rather archetypal, fetishist, unreasoning responses to questions of African agency and beingness. The Cesairean exhortation is to see and think clearly, and—an important word here: dangerously. We need a way to put to rest what burns in our souls in a blend of grief, regret, sorrow, anguish and denial; what we lost when one human culture chose to break its covenant of dignity with other human cultures, a psychic disruption that not only destroyed the codes of all human hospitality, but also calcified the human heart. The history we seek lies elsewhere, within the ruins and ghosts of what-could-have-been, inside the lives of descendantsurvivors of your insanity. Your ancestors brought into play some preternatural forces that they let run amok. These need to be understood and confronted in order to be returned to the metaphorical bottle. They need to be named. Naming is an act of an exorcism, and we definitely need that between us. Where else can we look for salvage? Inside old history. You have somehow conveniently ‘misplaced’ the stories of your much older culture of encountering varieties of Africa, whether through the multi-century German veneration of the unmistakeably African commander of a Roman legion, the Christian (before Europe’s own embrace of Christianity) Saint Maurice, who died in Aganum Switzerland, patron saint of the German Holy Roman Emperors, for whose lance, spurs and sword Henry the Fowler (919–936) ceded the Swiss canton of Aargau to an abbey and which were part of the regalia used at coronations of Austro-Hungarian emperors until 1916 (yes, the twentieth century). There were three early popes from the Roman province of Africa Proconsularis, and generals like Hannibal Barca and Scipio Africanus. A modern revisionism that pretends to an unbroken melaninfree cultural European line is rather daft, don’t you think? The easy pluralities and diversities of society seemed to have been the norm there as elsewhere. It leads us to the right and proper question: How did this change? What happened? Why is there still an army of zealots always disputing things even at the sites of the evidence of nonracist multiculturalism in Europe, although it wasn’t called that? But what happened? The plague? And whose bright idea was it to prioritise pigment and then entrench the psychosis of racism? When and where did the break occur? A shared wholeness? Is the repair of the consequentially tragic past lost to us? Of course not. We are humans imbued with an infinite imagination. We can race into realms where ten thousand worldviews that survived your onslaught still exist to read memories there. Out of these might a new grammar of history emerge. Is there a kinder more human future for and of and between us? Probably, and most likely under and through the China-originated BRI, since you are a part of it too. We are likely to re-encounter one another again, as Mandarin speakers. But more seriously. Some thinkers-on-trial work is required. Is your culture willing to poke at your Charles Darwin, John Locke, Carl Linneaus, Imannuel Kant? Not forgetting that completer of philosophy, too, the beloved Georg Hegel who boldly stated that ‘Man as we find him in Africa has not progressed beyond his immediate existence’. And we, the non-existent, in the Hegelian sense, have had to live out the belief of the Occident in this capsule of condensed stupidity. Will you be stoical as our scholars saw off the feet of your gurus and bring them down to their right and proper size? You seek to write a way into another future? Of this we are in agreement. But apart from panoptic-minded thinkers from across the disciplines, we shall need new words, fresh imaginings and imaging. We might also need to recover the old words that your ancestors and you blocked, mocked, derided. To this purpose, will you also allow representatives of the people your ancestors murdered, traumatised and wounded to meet you in an amphitheatre where memory and history throb, where the rites of repair and reconciliation can be effected? Will you allow yourselves to be silent and listen, or drink bitter herbs and eat the things, the sacraments that lead to wholeness? Will you learn also for your own sake, and the sake of your descendants? You know that we need an official armistice ceremony, probably in Berlin, to close the conference that launched the war against our worlds. We also need to co-create a liturgy of shared grief, a way to reconcile our ancestors, these wandering ghosts. We need to find another phrase to replace the benign ‘colonialism’. I propose ‘The Horror’— mostly out of mischief, to return to Europe that damn Conradian gaze. We would need to ‘do’ history differently: a muscular approach that is transformative and restorative of lost humanity. Scenario one I imagine a process made up of a legion of excellent-thinking persons representing the disciplines, who swear allegiance and belong to no nation, apart from the realm of History, Truth, Justice, Confession, Atonement and Reconciliation, who would oath themselves to the highest human values including integrity, courage, justice, truth, fearlessness. They would reopen the records of the old imperial companies and other private and commercial institutions with long colonial roots. They would audit the museums and collections, list the plundered assets of cultures and prepare a fee note. We are not talking about reparations yet. We mean the first order: the financial settling of outstanding historical accounts. Families and colonial company beneficiaries are known. The money trail is meticulous and the evidence lies in bank vaults. An audit and recovery of historical assets process becomes a necessity if historical truthfulness is to be reached, isn’t it? No one is demanding the trial of beneficiaries, although an apology and acknowledgment would be desirable as part of a reparative activity. The team would visit descendants, or host descendants; they would listen, archive, honour, witness, learn, record, collect, exhume, uncover, audit, analyse, reconstruct histories from communities. They would be film-makers, storytellers, dancers, data specialists, biochemists, anthropologists, photographers, coders … those needed to think, create, hear, imagine. They would develop new questions. They would deliver accountability reports to the nations. Second scenario Are the under-40s represented here? Are you? Flee. Run. Tear away from the elders of another generation, figuratively and metaphorically. Physically too. On your way out, raid the libraries, and pick out the literature that they ignore. Distill this and evolve a new grammar of action and thought system as you ruminate on the poetry and prophecies. Go beneath the surfaces and evolve a method to guide your original quest to restore humanity to wholeness. Exhume the graves the elders hide from you. Bring the cold bones in vaults up to the sun to be named and to be accounted for. Raid the museum storehouses. Rewrite the texts on walls where the bounty from atrocities are on display. That which should not be displayed in the first place, send home. Take the canon and set it aflame and see what endures. Dismantle the typologies, the boundaries and hedges that sustain a collective stupidity that is obsessed with dissipating truths. Write apology notes for assorted ancestors. Begin, at last, the real age of human discovery of the human and of the custodianship of the earth using the instruments of your time: technology, platforms, codes that confuse us. Judge us ruthlessly. Spare nobody. Doubt everything. Doubt me. Escape before you are seduced into inheriting the stench and weight of a billion ancient ghosts. Third option, aka, the storymaker’s fantasy This scenario is inspired by the aptly-named-for-this-moment novel, End of the Affair: Graham Greene has Maurice Bendrix, his protagonist, wrestle with a God that overwhelms everything he understands, a God that also seizes from him what he loves the most, and he gets to understand that this God is after him: he writes his relinquishment of the fight as a final prayer: I wrote at the start that this was a record of hate, and walking there beside Henry towards the evening glass of beer, I found the one prayer that seemed to serve the winter mood; ‘O God, You’ve done enough. You’ve robbed me of enough, I’m too tired and old to learn to love, leave me alone for ever.’ Standing here in the swirl of a long, long epoch of a toxic relationship with the Occident (its associates, its satellites, its proxies), I offer this prayer: not that you are God, although you have heretically appropriated that role for yourselves. To the Occident: You’ve done enough. You have plundered enough from us. You expect us to account for your inhumanity ad infinitum, to diagnose your pathologies and also deliver your absolution. We are weary and wary of you. The truth, unless you define it, is alien to your mind, goodness unless you decree it is alien to your conscience, as for beauty—see what your moneygrubbing, Mammon-worshipping choices have made of our earth. And like the planet, we are weary and wary of you. We are tired of bleeding every time we meet you. You are exhausting. Often, whenever you open your mouths in reference to us, bile and venom pour out, maledictions saturated with saccharine, as if you are the odious scions of the Three Witches of Macbeth. You are soul-draining. You feed off violence. You ease your corruption into laws that you then raise as sacrosanct. Your existential insecurity drives you to endlessly compare yourselves with others just to affirm that you are still at the summit of some fantastical pinnacle. Who cares? We are tired of your appetite for blood, your moral void, your soul loss, all those phantoms entrapped in your cold-glittering necropolis. Gaslighting, absurdity and amnesia: your preferred methods of interpreting us. We are exhausted by your theatre of innocence, your primordial resentments. Our spirits need distance to process the effect of the four centuries of your hungry-angry frenzy. We have our own, longstanding appointment with grief; the ghosts in and of our history will not let us rest. It is time for us to attend to them. We have a date with our history: we must learn how earth’s wealthiest continent, cradle and crucible of human knowledge and trade allowed itself to be bamboozled, bullied, weakened, possessed and disordered by a vicious, delusional, bubonicplague-tormented race that arrived at cosmopolitanism so, so late in history, whose primal parochialism keeps it superstitious about pluralism and diversity. Your insanity, its tenacity, do not matter to us anymore. With this in mind, apart from the basics of meet and greet, and the cool pragmatics of settling your 400-year-old outstanding business debt to us … Please … Leave us alone. Just leave us alone. (Lasse uns ... in Ruhe.) Acknowledgement ‘Derelict Shards: The Roamings of Colonial Phantoms’ by Yvonne Adhiambo Owuor. Copyright © 2020, Yvonne Adhiambo Owuor, used by permission of The Wylie Agency (UK) Limited. No changes shall be made to the Work without the written consent of Yvonne Adhiambo Owuor or her representative. No further use of this material in extended distribution, other media, or future editions shall be made without the express written consent of The Wylie Agency. All rights not expressly granted herein are hereby reserved and retained by Yvonne Adhiambo Owuor. Notes https://bloomberg.com/news/articles/2020-03-11/pandemic-bond-investors-brace-forwipeout-ascoronavirus-spreads; https://www.washingtonexaminer.com/news/425m-in-world-bankcatastrophe-bonds-set-to-default-if-coronavirusdeclared-apandemic-by-june; https://www.ft.com/content/70dd05ac-54d811ea-8841-482eed0038b1; https://development/2020/feb/28/worldbanks-500m-coronavirus-push-toolate-forpoor-countries-experts-say. autopsy (n.) 1650s, ‘an eyewitnessing, a seeing for oneself’, from Modern Latin autopsia, from Greek autoptēs, ‘a seeing with one’s own eyes’, from autos, ‘self’, (see auto-) + opsis, ‘a sight’ (from PIE root *okw, ‘to see’). That is my attempt to extend the many meanings of It was shipped into necropsy, which is still OK. The idea of colonialism as an always morphing phantom that needs to be exorcised/ autopsied, faced fearlessly. I like the dimensions of that word. ‘The tragedy of Africa is that the African has not fully entered into history ... The African peasant … only knew the eternal renewal of time, marked by the endless repetition of the same gestures and the same In this realm of fancy ... there is neither room for human endeavour nor the idea of progress … This man never really launched himself into the future,’ 27 July 2007, Nicolas Sarkozy, speech at Cheikh Anta Diop University in Dakar, Senegal. https://www.africaresource. com/essays-a-reviews/essays-adiscussions/437-the-unofficial-english-translation-of-sarkozys-speech. https://theguardian.com/ world/2020/aug/12/namibia-rejects-german-compensation-offer-over-colonialviolence; https:// ny-reparations/a-54535589.